2021
DOI: 10.1021/acs.chemmater.1c00315
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of Ultrasmooth, Precisely Shaped Gold Nanospheres via Surface Self-Polishing Etching and Regrowth

Abstract: Despite many seeded methods having been achieved to synthesize spherical nanoparticles, the one-pot synthesis of Au nanospheres with perfect morphology is still a challenge due to nanocrystals tending to adopt a polyhedral morphology to minimize their surface free energy. We present here a one-pot synthesis for precisely shaped and monodispersed single-crystalline Au nanospheres with an ultrasmooth surface and tunable sizes (30–100 nm). During the synthesis, Au nanospheres undergo a unique morphology change fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 59 publications
1
30
0
Order By: Relevance
“…S1e †) and the strong plasmonic coupling effect of their assembled gold oligomers. 45 It can also be found that the extinction properties of these gold oligomers are well consistent with the color changes in these bands. 46 All results indicate that the components of these gold oligomers in bands I to IV should be the assemblies of small-sized gold nanospheres.…”
Section: Resultssupporting
confidence: 57%
“…S1e †) and the strong plasmonic coupling effect of their assembled gold oligomers. 45 It can also be found that the extinction properties of these gold oligomers are well consistent with the color changes in these bands. 46 All results indicate that the components of these gold oligomers in bands I to IV should be the assemblies of small-sized gold nanospheres.…”
Section: Resultssupporting
confidence: 57%
“…100 particles were measured to obtain the size distribution histogram of each sample. 51,52 The size is 16.4 ± 1.5 nm for PtSn 4 , 24.5 ± 1.5 nm in width and 5 ± 1.6 nm in length for PtSn 2 , 7.3 ± 1.3 nm for PtSn, 4.3 ± 0.97 nm for Pt 3 Sn, and about 3 nm for commercial Pt/C 53 (Fig. S1-4 †), respectively.…”
Section: Resultsmentioning
confidence: 98%
“…The purified ligand-modified Au nanoplates were redispersed in 500 μL of 0.2 M CTAB solution. Then, HAuCl 4 (5,10,15, or 20 μL, 2 mg/mL) was added to the Au nanoplate solution under vigorous stirring. The etching solution was kept at 30 °C for 3 h.…”
Section: ■ Introductionmentioning
confidence: 99%